The Effectiveness of Fathers' Roles in Early Childhood Parenting at TK Raudatul Qur’an - Khairani, Mesra; Febrianti, Yeni Elviza; Pasaribu, Mhd. Donal; Rosni, Astri Alfina (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2023)
Fathers also make an important contribution to a child's development, the experiences shared with a father will influence a child into adulthood. Although research on fathers has continued to increase over the past three decades, research discussing the family has focused more on the mother figure (Roggman, et al, 2002). This research aims to obtain a descriptive picture of the role of fathers in child care. and in collecting data using a questionnaire in the form of open questions that will reveal the father's parenting from the father's own perspective. A total of 20 parents of students at Kindergarten Raudatul Qur'an were involved in this research. The results of this research describe the parenting process which involves the role of the father (fathering). The joint responsibility of fathers and mothers in carrying out parenting roles is quite high, because 86% of respondents stated that caring for children is a joint task. The findings regarding the average time fathers spend interacting with their children is 6 hours. In terms of quantity, it can be said that the father's time with the child is sufficient to carry out activities together with the child. One of the important roles of fathers in the family is economic provider, so that on work holidays some still carry out activities to earn a living with side jobs.